1994
DOI: 10.1177/104239159400600103
|View full text |Cite
|
Sign up to set email alerts
|

Extinguishment of Class B Flames by Thermal Mechanisms; Principles Underlying a Comprehensive Theory; Prediction of Flame Extinguishing Effectiveness

Abstract: Flame quenching by condensed or gaseous extinguishants and by external sources is examined. The quenching by extinguishants is due to heat-absorption sinks—dissociation, decomposition, vaporization, and heat capacity. External quenching by water-cooled metal surfaces or by radiation to surroundings is shown to have common properties with internal quenching by extinguishant particles or molecules.Flame-extinguishing mechanisms are effectively explained with thermal quenching concepts and a flame heat bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The chemical and thermal aspects associated with the inhibition mechanism of various fire retardants are discussed by da Cruz et al (1988), Ewing et al (I989a), Birchall (1970), Ewing et al (1992), and Ewing et al (1994. Ewing et al (1989a) analyzed experimental data obtained by various investigators and concluded that the extinction of diffusion flames by most of the inhibiting agents including NaHC0 3 can be attributed to thermal heat absorption effects such as heat-capacity sinks and decomposition/vaporization sinks.…”
Section: Resul1s and Discussionmentioning
confidence: 97%
“…The chemical and thermal aspects associated with the inhibition mechanism of various fire retardants are discussed by da Cruz et al (1988), Ewing et al (I989a), Birchall (1970), Ewing et al (1992), and Ewing et al (1994. Ewing et al (1989a) analyzed experimental data obtained by various investigators and concluded that the extinction of diffusion flames by most of the inhibiting agents including NaHC0 3 can be attributed to thermal heat absorption effects such as heat-capacity sinks and decomposition/vaporization sinks.…”
Section: Resul1s and Discussionmentioning
confidence: 97%
“…It can be used to hit the flames, the hot gases produced, the heated surfaces of the room, the fuel surface and the fuel not yet involved in the fire. Cooling of the fuel and stopping fuel gasification is the main mechanism when applying the water at the fuel surface [9,10], and cooling of the flames below the adiabatic flame temperature is the main mechanism when applying water droplets into the flames [11]. There are also other effects, e.g., the stirring of fire gases due to the water flow and to the generation of steam.…”
Section: Techniques Of Water Applicationmentioning
confidence: 99%
“…Physical (endothermic) modes of action have been shown to be of dominant importance in the flame-retardant action of a wide range of non-phosphorus-containing volatile compounds (38,39).…”
Section: Vapor-phase Mechanismsmentioning
confidence: 99%